2001
DOI: 10.1149/1.1386627
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Improvement of the Microstructure of Chemical Vapor Deposited Aluminum on Silicon Carbide

Abstract: This paper presents results on the chemical vapor deposition of aluminum on silicon carbide starting from triisobutylaluminum. The deposited films show important systematic trends in surface roughness and porosity. Considering literature information on the deposition of aluminum on silicon, pretreatments of the deposition surface with hydrofluoric acid and/or titanium tetrachloride have been tested. They lead to films with a smoother morphology and stronger adhesion with the substrate than in the case of an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…This is in agreement with the high value of Rz of this sample. This morphology was also observed for Al films deposited on polished bulk Al substrates and on SiC15 and is characteristic of the previously mentioned trends concerning the competition between nucleation and growth of CVD‐processed Al films.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This is in agreement with the high value of Rz of this sample. This morphology was also observed for Al films deposited on polished bulk Al substrates and on SiC15 and is characteristic of the previously mentioned trends concerning the competition between nucleation and growth of CVD‐processed Al films.…”
Section: Resultssupporting
confidence: 79%
“…A major concern of MOCVD‐processed Al films is the often rough microstructure obtained due to the reluctance of Al to nucleate on silicon and silicon‐based ceramic surfaces. This behavior has been extensively reported in the literature and has been faced, at least partially, through appropriate treatments of the involved surfaces (see the literature15 and references therein). The nature of the Al precursor also influences the resulting film morphology.…”
Section: Resultsmentioning
confidence: 88%
“…Figure 2 presents the Arrhenius plot of DMEAA deposition on bare Ti6242 at 1330 Pa. From this diagram, activation energy of 0.3 eV was measured. The DMEAA processed coating, AlD1, exhibits an average roughness of 0.5 m and a continuous base similar with results found by Vahlas et al 11 Neither preferential orientation nor carbon contamination could be observed in AlD1.…”
Section: Methodssupporting
confidence: 88%
“…Vahlas et al 11 reported that MOCVD processed Al coatings from TIBA on silicon carbide strongly depend on surface pretreatments. Deposition on Ti6242 is more straightforward as nucleation is easier on metallic surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods are developed for the production of Al and Al-containing thin films, among which chemical vapor deposition (CVD) combines high growth rates and conformal coverage of complex surfaces (Thomann et al, 2011). However CVD processed Al films suffer from a rough microstructure, despite efforts made to attenuate it (Vahlas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%